Analisis Pengaruh Budaya Pembelajaran Dan Penerapan Problem Based Learning Terhadap Prestasi Akademik Siswa: Analysis of the Influence of Learning Culture and Implementation of Problem-Based Learning on Students' Academic Achievement - Osman, Isnawati; Sembiring, Darmawanta; Aziz, Firman; Asmarany, Anugriaty Indah; Wulandari, Ayu Ratna; Priambodo, Caka Gatot (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
The achievements achieved by students not only impact the students but, of course, also impact the educational institutions where the students attend school. The many academic achievements obtained by students will be beneficial not only for the image of educational institutions but also for various other positive things such as accreditation status and evaluation of school performance. Students' academic achievement will encourage students to continue to improve their competence and form a competitive spirit. This study examines and analyzes the role of learning culture and the application of problem-based learning on student academic achievement. This research is qualitative, where researchers conduct interviews and observations in collecting data. In addition, this study uses literature and previous research studies that discuss the same variables and problems, namely those related to student academic achievement. The unit of analysis in this study includes students at the high school level in Indonesia, while the observation unit involves teachers, principals, and parents of students. This study concludes that building a learning culture that is pro or supports the adoption and use of technology and digitalization in the learning process and the application of problem-based learning can create and improve student academic achievement. The research suggests that school management should continue facilitating and encouraging teachers and students to optimize a learning culture oriented toward technology and digitalization. Teachers are also encouraged to maintain their performance in realizing learning oriented towards problem-based learning to improve students' academic achievement.